‘Effectivités’: an imperative legal principle in resolving the Senkaku/Diaoyu Islands dispute - Ali Mohamed, Ashgar Ali; Ansari, Abdul Haseeb; Ahmad, Muhamad Hassan (The Indian Law Institute, 2018)
Since 1971, China, Taiwan and Japan have been claiming sovereignty on Senkaku/Diaoyu Islands in the East China Sea. These islands have been the subject matters of dispute due to the existence of oil deposits underneath and also being strategic location for exploitation of oil and gas resources in the region. China claims historic title over the Diaoyu Islands, as these have been inherent part of it since ancient times. It further contends that islands were seized by Japan during the 1895 Sino-Japan War. On the other hand, Japan concedes that it had occupied the Senkaku Islands since 1895 while these islands were terra nullius and totally uninhibited prior to that time. Besides, China had never challenged Japanese exercise of sovereignty over these islands until 1971 in which the United Nations reported to have substantial oil and gas reserves in the area. As far as contemporary international adjudication is concerned, a state has immense prospect of having title over the territory if it can prove the exercise of state sovereignty and ‘effective control’ (effectivités) over the disputed territory. This is because international courts and tribunals, in practice, predominantly draw attention solely on the element of effective control in deciding the territorial and boundary disputes in spite of having various modes and concepts of acquisition of territory under international law. Accordingly, this paper analyses critically the judicial interpretation and application of the principle of ‘effectivités’ by the international courts and tribunals in resolving inter-state territorial and boundary disputes. Additionally, it applies the principle to the Senkaku/Diaoyu Islands dispute, and finally offers some amicable solutions to address the dispute among the parties in peaceful manners under the purview of international law.